The impact of energy refurbishment interventions on annual energy demand, indoor thermal behaviour and temperature-related health risk. (June 2021) - Etxebarria-Mallea, Matxalen; Oregi, Xabat; Grijalba, Olatz; Hernández-Minguillón, Rufino
Abstract: The reduction of energy consumption in the built environment by energy renovation strategies is an important target to deal with buildings sector's negative impact on our planet. Regardless of the potential for energy and emissions savings, building renovation has other relevant effects on users' quality of life and health that has not been so well assessed. The present study aims to contribute to current building energy efficiency targets, particularly to Spanish residential building sector, from a still non-existing integrated vision. To this end, an evaluation method was developed to discuss the impact of energy renovation interventions on annual energy demand, indoor thermal comfort and indoor thermal health risk variation. The approach was applied to an open linear residential block located in the Basque Country (northern Spain), and twelve scenarios based on three variables were analysed using DesignBuilder tool. The results obtained show a clear contrast in the impacts caused by energy refurbishment interventions. In particular, the generalized decrease in the number of hours in which indoor temperatures are within comfortable ranges is significant in contrast to the noteworthy reduction in annual energy demand. In conclusion, the results suggest new factors to be considered when updating energy renovation policies. Highlights: Integrated evaluation of the impact of energy refurbishment interventions. Relationship between energy demand and thermal comfort level variation. Influence of diverse indoor thermal comfort requirements on energy demand. Influence of energy refurbishment strategies on indoor thermal health risk. Questionable suitability of current energy refurbishment regulations towards health.